2022
DOI: 10.3389/fmed.2022.957557
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of endoscopic ultrasound in the diagnosis of gallbladder lesions

Abstract: Gallbladder tumors are neoplastic lesions; however, it can be difficult to distinguish between benign and malignant gall bladder tumors before surgery, although endoscopic ultrasound (EUS) is useful for differentiation. Fundamental B mode EUS (FB-EUS) and contrast-enhanced harmonic EUS (CH-EUS) are reported to be useful for the diagnosis of gallbladder tumor because they allow evaluation of polypoid lesion and gallbladder wall thickening. Scoring systems based on FB-EUS imaging are available for the diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…CH-TUS with second-generation contrast agents makes it easier to detect the target because the microbubbles are not destroyed by continuous observation using low sound pressure [41][42][43]. Previous studies have examined the utility of Sonazoid-based CH-TUS in the characterization of the liver [44,45] and GB lesions [9,[46][47][48][49][50][51][52][53]. Some studies have shown that CH-TUS can overcome the limitations associated with conventional TUS and increase the diagnostic accuracy of GB diseases (the accuracy of CH-TUS and conventional TUS was 95.2% and 88.6%, respectively) [47,52].…”
Section: Contrast Harmonic Imaging (Ch-imaging) (I) Ch-tusmentioning
confidence: 99%
See 1 more Smart Citation
“…CH-TUS with second-generation contrast agents makes it easier to detect the target because the microbubbles are not destroyed by continuous observation using low sound pressure [41][42][43]. Previous studies have examined the utility of Sonazoid-based CH-TUS in the characterization of the liver [44,45] and GB lesions [9,[46][47][48][49][50][51][52][53]. Some studies have shown that CH-TUS can overcome the limitations associated with conventional TUS and increase the diagnostic accuracy of GB diseases (the accuracy of CH-TUS and conventional TUS was 95.2% and 88.6%, respectively) [47,52].…”
Section: Contrast Harmonic Imaging (Ch-imaging) (I) Ch-tusmentioning
confidence: 99%
“…Thus, CH-EUS is a useful approach that addresses the limitations of CH-TUS. The usefulness of CH-EUS in the diagnosis of pancreatic [56][57][58][59][60][61], gastrointestinal [62,63], and GB lesions [9,[46][47][48][49][50][51][52][53] has been reported. CH-EUS is useful for diagnosing GB wall thickening.…”
Section: (Ii) Ch-eus (Table 4)mentioning
confidence: 99%
“…However, acute cholecystitis[ 53 ] and biliary peritonitis[ 54 ] have been reported following FNA of a GB mass and after bile aspiration, respectively. Tamura et al [ 55 ] have proposed an approach considering the risk of EUS-FNA in cases of GB masses (Figure 8 ): Start by obtaining tissue via an ERCP-guided biopsy, then perform EUS-FNA from metastatic liver lesions or lymph nodes when present, and conclude with EUS-FNA from the GB mass itself. Similarly, during the FNA procedure and puncturing the GB wall, it is essential to gain stroke distance by tangentially puncturing the GB wall, avoiding puncture through the lumen.…”
Section: Practical Applications Of Eus In Gb Diseasesmentioning
confidence: 99%
“…This has limited its application in the diagnosis of GB lesions. Furthermore, even though the few conducted studies have not reported major complications related to the use of this type of EUS in the diagnosis of GB pathologies, the risk of bleeding and tumor seeding are still high with the continuous use of EUS in the diagnosis of GB pathologies such as GB cancer[ 55 , 58 ].…”
Section: Limitations Of Linear Eus Use In the Diagnosis Of Gallbladde...mentioning
confidence: 99%